Ratones knock-out del receptor lpa1 de ácido lisofosfatídico presentan un acusado déficit de la isoenzima glutaminasa KGA (GLS) y una morfología alterada en las espinas dendríticas de hipocampo y corteza - Peñalver, Ana; Campos-Sandoval, José Ángel; Sánchez-Varo, Raquel María; Cardona Ramírez, Carolina; Castilla, Laura; Blanco, Eduardo; Martín-Rufián, Mercedes; Segura-Checa, Juan Antonio; Mates-Sánchez, José Manuel; Alonso-Carrión, Francisco José; Gutiérrez-Pérez, Antonia; Rodriguez-de-Fonseca, Fernando; et al. (My University, 2015)
Objectives: The objective of the present study was to utilize mice with knocked-down lysophosphatidic acid 1 (LPA1) receptor to ascertain changes in glutamatergic transmission that may help to explain part of the cognitive and memory deficits shown by these KO-LPA1 mice. Material & methods: A well characterized KO-LPA1 mouse strain was used as animal model and compared with wild-type (WT) and heterozygous animals. Expression studies were implemented by immunohistochemistry and Western analysis of mouse brain regions, real-time quantitative RT-PCR of GA isoforms, enzymatic analysis of regional GA activity and Golgi staining to assess dendritic spine morphology and density. Results: A strong reduction of KGA immunoreactivity was mostly revealed in cerebral cortex and hippocampus of KO-LPA1 mice versus WT and heterozygous animals. In contrast, neither mRNA levels nor enzyme activity were significantly altered in KO mice suggesting compensatory mechanisms for neurotransmitter Glu synthesis. Interestingly, Golgi staining of hippocampal and cortical neurons revealed a clear morphology change toward a less-mature undifferentiated spine phenotype, without changes in the total number of spines. Conclusions: The molecular mechanisms underlying KGA downregulation in null LPA1 mutant mice are unknown. However, LPA increases neuronal differentiation, arborization and neurite outgrowth of developing neurons, while Gln-derived Glu, through GA reaction, has been also involved in neuronal growth and differentiation. It is tempting to speculate that downregulation of KGA protein in KO-LPA1 mice induce morphological changes in dendritic spines of cortical and hippocampal neurons which, in turn, may account for memory and cognitive deficits shown by KO-LPA1 mice.
Keywords: Isoenzimas; Glutaminasa; Ácido lisofosfatídico; Modelos animales Knockout; Hipocampo; Plasticidad sináptica